Pengaruh Beban Kerja, Stres Kerja, dan Motivasi terhadap Kinerja Karyawan RS Ludira Husada Tama Yogyakarta - Gabriela Kartika Y.S.A; Sri Haryani (Telaah Bisnis, 2020)
Abstract Organizations or companies need human resources to carry out all business activities, both related to operations, marketing, finance, human resources, and information systems. Human resources are believed to be one of the key factors in achieving superior organizational performance. Of the various factors that must be considered to achieve this performance are workload, work stress, and motivation. This study aims to analyze the effect of work load, work stress, and motivation on RS Ludira Husada Tama employee’s performance.The number of samples was 110 respondents, data collection using questionnaires, and using linear regression analysis. The results in this study indicate: workload and motivation variables partially affect employee performance; workload, work stress, and motivation variables simultaneously influence employee performance; of the three variables; the biggest influence on employee’s performance is the workload variable. Overall, workload, work stress, and motivation variables contributed to the influence of 26.4% while the remaining 73.6% was influenced by other variables not included in the research model.